Wild Plants Drive Biotic Differentiation Across Urban Gardens - Aaron N. Sexton; Felix Conitz; Ulrike Sturm; Monika Egerer (Ecology and Evolution)
ABSTRACT The Urban Biotic Homogenization (UBH) hypothesis predicts that ecological communities should become increasingly similar in their species composition across an urbanization gradient, and that spatially independent cities should be more similar in species composition to each other than they are to their surrounding rural communities. However, there is conflicting scientific evidence for these predictions. Using 4 years of plant community data in 30+ urban community gardens across two European cities, we find no support for this hypothesis, especially among spontaneous, or wild plant species. Wild plant species exhibited increased biotic differentiation with urbanization (i.e., increased beta diversity), and plant species community composition was significantly different between the two cities. Wild plant species contributed more to overall beta diversity compared to cultivated plant species. These findings suggest that wild plant species may combat urban biotic homogenization in garden ecosystems and should therefore be supported to increase urban ecological heterogeneity.